A Plasmodium berghei reference line that constitutively expresses GFP at a high level throughout the complete life cycle. - Franke-Fayard, B; Trueman, H; Ramesar, J; Mendoza, J; van der Keur, M; van der Linden, R; Sinden, R; Waters, A; Janse, C (2004)
Green fluorescent protein (GFP) is a well-established reporter protein for the examination of biological processes. This report describes a recombinant Plasmodium berghei, PbGFPCON, that constitutively expresses GFP in a growth responsive manner in its cytoplasm from a transgene that is integrated into the genome and controlled by the strong promoter from a P. berghei elongation factor-1alpha gene. All life cycle forms of PbGFPCON except for male gametes can be easily visualized by fluorescent microscopy. PbGFPCON showed similar growth characteristics to wild type P. berghei parasites throughout the whole life cycle and can therefore be used as a reference line for future investigations of parasite-host cell interactions. The principle of automated fluorescence-based counting and sorting of live parasites from host cell backgrounds and different parasite forms from complex mixtures such as asynchronous blood stages is established. PbGFPCON allows the visualization and investigation of live parasite stages that are difficult and labor-intensive to observe, such as the liver and mosquito stages. PbGFPCON can be employed to establish the phenotype of independent mutant parasites. With the recent development of a second, independent selectable marker in P. berghei, PbGFPCON is a useful tool to investigate the effect of further genetic modifications on host-parasite interactions.